The Somatotype of Martial Athletes in the Fighter Category Against Achievement - Didi Suryadi; Uray Gustian; Ella Fauzia (STKIP Muhammadiyah Kuningan, 2022)
This study aims to determine the effect of the somatotype of the Tarung Derajat martial arts athlete in the Fighter category on achievement. Quantitative descriptive research using survey method. Anthropometric manual tests and measurements to determine the athlete's body type. The research sample consisted of 8 male athletes and 7 female Tarung Derajat Fighters in the West Kalimantan category, held at the Satlat Mujahiddin, Pontianak City. The data obtained in the field is the results of the somatotype measurement test and the achievement of Tarung Derajat athletes, then analyzed using descriptive percentages to analyze. The study results were 46% with endomorph mesomorph body type, 40% central, 7% endomorph, and 7% ectomorph mesomorph with local, national, and international achievements. The conclusion is that there is no influence between the somatotypes of the Tarung Derajat martial arts athletes in the Fighter category on achievement.